2017
DOI: 10.5004/dwt.2017.21383
|View full text |Cite
|
Sign up to set email alerts
|

Removal/separation of Co(II) ion from environmental sample solutions by MnFe2O4/bentonite nanocomposite as a magnetic nanomaterial

Abstract: a b s t r ac tMnFe 2 O 4 /bentonite nanocomposite was synthesized by chemical co-precipitation method. The prepared nanocomposite was characterized by X-ray diffraction (XRD), vibrating sample magnetometer (VSM) and scanning electron microscopy (SEM) techniques. The XRD results indicated the montmorillonite associated with quartz phases in the structure of MnFe 2 O 4 /bentonite nanocomposite synthesized. VSM was carried out to characterize the magnetic properties of the nanocomposite prepared. SEM images of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Table 3 showed the results obtained from these experiments, and it was concluded that the variation of the resin dosage produced an increment in the percentage of cobalt(II) loaded onto the resin, but at the same time the metal uptake decreased. These results were used to estimate the equilibrium isotherm, and the results from this fit indicated that the experimental results were best represented by the Langmuir model (r 2 = 0.9612) (Daraei and Mittal, 2017;Rahmani et al, 2017):…”
Section: Cobalt(ii) Loading Onto Lewatit Tp260mentioning
confidence: 99%
“…Table 3 showed the results obtained from these experiments, and it was concluded that the variation of the resin dosage produced an increment in the percentage of cobalt(II) loaded onto the resin, but at the same time the metal uptake decreased. These results were used to estimate the equilibrium isotherm, and the results from this fit indicated that the experimental results were best represented by the Langmuir model (r 2 = 0.9612) (Daraei and Mittal, 2017;Rahmani et al, 2017):…”
Section: Cobalt(ii) Loading Onto Lewatit Tp260mentioning
confidence: 99%
“…Rahmani et al used co-precipitation to make a magnetic nanocomposite of MnFe 2 O 4 and bentonite that can adsorb Co(II) ions from wastewater. The nanocomposite proved to be very good at adsorbing Co(II) ions, which suggests that it could be an effective way to get heavy metals out of polluted water [21]. Chen et al developed Fe 3 O 4 /CNTs magnetic nanoparticles that effectively eliminated Cr(VI) from wastewater.…”
Section: Introductionmentioning
confidence: 99%
“…The efficient removal of arsenic from water using granular sorbent Fe–Mn binary oxide-impregnated chitosan beads was reported by Qi et al [ 23 ]. The separation of Co (II) ions from environmental sample solutions by a MnFe 2 O 4 /bentonite nanocomposite (a magnetic nanomaterial) was described by Rahmani et al [ 24 ]. Muliwa et al [ 25 ] reported manganese removal from water using chitosan/bentonite/MnO composite beads.…”
Section: Introductionmentioning
confidence: 99%